The Differential Representation of Latina and Black Female Victims in Front-Page News Stories: A Qualitative Document Analysis. (October 2019) - Slakoff, Danielle C.; Brennan, Pauline K.
Critical race feminists posit that perceptions of White and minority females differ, which suggests that media representations will vary among female crime victims. To explore this proposition, we examined front-page crime stories from four different U.S. newspapers using Altheide's approach to qualitative document analysis. We found that stories about White female victims received more repeated coverage and were more likely to contain sympathetic narratives than stories about Latina/Black female victims. In contrast, Latina/Black female victims were more likely to be portrayed as risk-takers and "bad" women, and their victimization was normalized through descriptions of their unsafe environments.